Pengajaran Etika Kristen dalam Pembentukkan Karakter dan Moral Siswa di SMTK Setia Mamuju - Sarumaha, Lia Arini; Mantiri, Lyly grace (Jurnal PKM Setiadharma, 2025)
Character and moral education is an important element in shaping students' personalities, especially in Christian-based schools such as SMTK Setia Mamuju. This research aims to explore how the teaching of Christian ethics can be applied effectively in shaping students' character and morals. The research uses a qualitative method with a descriptive approach, where data is collected through interviews, observations and document analysis. The results of the study show that the teaching of Christian ethics not only focuses on teaching biblical doctrine but also on the application of values such as love, responsibility, honesty and discipline in students' daily lives. Christian Religious Education Teachers (PAK) play an important role as role models and facilitators in the process of shaping students' character. The strategies used include integrating Christian values into the curriculum, Bible-based interactive learning, and character development through extracurricular activities. In conclusion, the teaching of Christian ethics at SMTK Setia Mamuju has proven to be effective in building students' character and morals, but continuous efforts are still needed to ensure consistency in its implementation. This study provides recommendations for educators to strengthen a holistic and contextual teaching approach in character education based on Christian ethics.